2021
DOI: 10.1039/d1ra01135a
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical platform based on a hemin–rGO–cMWCNTs modified aptasensor for sensitive detection of kanamycin

Abstract: An electrochemical aptasensor based on hemin–rGO–cMWCNTs was established. The aptasensor exhibited a low detection limit and a wide linear range. Excellent stability, reproducibility and applicability were presented for KANA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A comparison between determinations of KANA using different sensors was investigated and is shown in Table 1. It was found that the LOD calculated using the proposed sensor (0.161 nM) is the lowest among those obtained by surface plasmon resonance using a molecularly imprinted polymer (LOD in milk is 43.3 nM and honey is 12.0 nM), 26 ESI using MIP/GO/Ppy (5.0 nM), 27 DPV using MMIPs/MGCE (4.88 nM), 28 DPV using Apt/Co/Ni-Bio-MOF and Au-doped coral-like ZrO 2 (37 nM), 35 EIS using Apt/CB/CHIT/GCE (0.3 nM), 36 SWV using UiO-66-NH 2 /MCA/MWCNT@rGONR/GCE (13.0 nM), 37 DPV using Fc/β-CD-SH/Au@Fe 3 O 4 /GCE (1.87 nM), 38 DPV using Apt/ hemin-rGO-cMWCNTs/GCE (0.36 nM), 39 and colorimetry using the peroxidase-like activity of oxygen-terminated few-layered Ti 3 C 2 Tx MXene (15.28 nM). 40 In conclusion, the proposed sensor shows many advantages over other reported sensors for the deter-mination of KANA including the lowest detection limit, a wide linear range, and cost-effectiveness.…”
Section: Analytical Performance Of the Kana-mip/cpementioning
confidence: 99%
“…A comparison between determinations of KANA using different sensors was investigated and is shown in Table 1. It was found that the LOD calculated using the proposed sensor (0.161 nM) is the lowest among those obtained by surface plasmon resonance using a molecularly imprinted polymer (LOD in milk is 43.3 nM and honey is 12.0 nM), 26 ESI using MIP/GO/Ppy (5.0 nM), 27 DPV using MMIPs/MGCE (4.88 nM), 28 DPV using Apt/Co/Ni-Bio-MOF and Au-doped coral-like ZrO 2 (37 nM), 35 EIS using Apt/CB/CHIT/GCE (0.3 nM), 36 SWV using UiO-66-NH 2 /MCA/MWCNT@rGONR/GCE (13.0 nM), 37 DPV using Fc/β-CD-SH/Au@Fe 3 O 4 /GCE (1.87 nM), 38 DPV using Apt/ hemin-rGO-cMWCNTs/GCE (0.36 nM), 39 and colorimetry using the peroxidase-like activity of oxygen-terminated few-layered Ti 3 C 2 Tx MXene (15.28 nM). 40 In conclusion, the proposed sensor shows many advantages over other reported sensors for the deter-mination of KANA including the lowest detection limit, a wide linear range, and cost-effectiveness.…”
Section: Analytical Performance Of the Kana-mip/cpementioning
confidence: 99%
“…25 Through π-π interactions, hemin could be immobilized on the surface of rGO to form H-rGO nanocomposites, which not only prevents the agglomeration of rGO, but also can be used as an electroactive substance because of the reversible redox properties of hemin's Fe(III)/Fe(II). 26 In addition, precious metal nanoparticles (e.g., Au, Ag, Pt, and Pd nanoparticles) are useful in various biosensors because the nanostructure of metal nanoparticles on the electrode surface can improve the surface area and mass transport as well as increase the load of fixed biomolecules. 27 For example, PtNC-multi-walled carbon nanotube-graphene nanoparticles (PtNC-MWCNT-GNPs) have been used to simultaneously detect ascorbic acid and dopamine.…”
Section: Introductionmentioning
confidence: 99%
“…25 Through π–π interactions, hemin could be immobilized on the surface of rGO to form H-rGO nanocomposites, which not only prevents the agglomeration of rGO, but also can be used as an electroactive substance because of the reversible redox properties of hemin's Fe( iii )/Fe( ii ). 26…”
Section: Introductionmentioning
confidence: 99%
“…2,3 It should be pointed out that the residual Kana in foods or the environment will eventually lead to its accumulation in the human body, which may cause some diseases such as hepatosis, epicophosis and respiratory failure. 4 The European Union and China have explicitly stipulated the maximum residue standard of Kana in products as 150 μg kg −1 and 200 μg kg −1 respectively. 5 Thus, the sensitive monitoring of residual Kana is an urgent need and a significant challenge.…”
mentioning
confidence: 99%